Online Learning Interaction Continuum (OLIC): A Qualitative Case Study - Mohd Hashim, Mohamad Hisyam (International Education Studies, 2011)
The purpose of this research project is to explore the use of Blackboard Learning System (BLS) in enhancing interaction in online teaching and learning enviornment. This paper discusses the conceptual framework of Online Learning Interaction Continuum (OLIC) which explains the five levels of interactions. The OLIC was conceptualized as a result of a qualitative case study conducted at one of the university in Malaysia. The OLIC model consists of five levels of interaction beginning with level 1, the lowest level through level 5, the highest level. The levels are lecturer-interface interactions, lecturer-content interactions, lecturer-support interactions, learner-interface interactions and lecturer-context interactions. They state the challenges faced in the interactions such as facilities, time, knowledge and skill and policies and procedures, participation, interest, online instructional strategies and content. The research project demonstrated the importance of the level of interactions to implement Learning Management System (LMS) in teaching and learning in the higher institutions of learning